2006
DOI: 10.1002/ajh.20733
|View full text |Cite
|
Sign up to set email alerts
|

Inherited thrombophilia is associated with deep vein thrombosis in a Colombian population

Abstract: The development of venous thromboembolism is influenced by a variety of genetic and environmental risk factors. A few studies have ascertained whether thrombophilic defects are risk factors for venous thromboembolism in Latin American populations with a variable degree of admixture, such as the Colombian population. To address this issue, we conducted a case-control study involving 100 consecutive patients with deep vein thrombosis and 114 healthy controls from the Hospital Universitario San Vicente de Paú l, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 32 publications
2
16
1
6
Order By: Relevance
“…Similar to the frequency findings of this study, in Colombia, the FII G20212A mutation was not detected at all (0% frequency) and only 0.43% of the subjects in that study had the FV G1691A mutation (Torres et al, 2006). Likewise, in a study conducted in Chile (N = 1200), only 1% of the population had any variant alleles (Palomo et al, 2009).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Similar to the frequency findings of this study, in Colombia, the FII G20212A mutation was not detected at all (0% frequency) and only 0.43% of the subjects in that study had the FV G1691A mutation (Torres et al, 2006). Likewise, in a study conducted in Chile (N = 1200), only 1% of the population had any variant alleles (Palomo et al, 2009).…”
Section: Discussionsupporting
confidence: 85%
“…The relationship between MTHFR C677T and the development of VTE remains unclear because, despite the failure of several studies to show an association (NizankowskaMogilnicka et al, 2003;Almawi et al, 2005;Torres et al, 2006;Alfirevic et al, 2010), in a meta-analysis of 8364 subjects, Den Heijer et al (2005) concluded that the presence of the TT genotype poses a 20-fold greater risk for VTE than the CC genotype. One consequence of the MTHFR C677T polymorphism is a resultant increased plasma level of homocysteine, a condition considered to be an independent risk factor for VTE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 The major prevalence of FV Leiden and PT G20210A in the Caucasian population supports the theory that both mutations emerged 21.000 to 34.000 years ago, only in the Caucasian population, after the separation of Mongols and Caucasian. 6,8 The revision of 26 European and neighboring countries showed that the FV Leiden could have expanded from the region of Anatolia, Turkish peninsula, 3,26 to Europe and to other continents later.…”
Section: Discussionmentioning
confidence: 99%